Diagnosing the Problems in Teaching Courses of English for Specific Purposes at the University of Prishtina and Private Colleges in Kosovo - Husaj, Shqipe (European Journal of Social Science Education and Research, 2021)
A number of academic units at the University of Prishtina (UP) offer English for specific purposes in order to address the needs of students to communicate effectively in their chosen field of study. Recent developments and the changing landscape of teaching and learning English for Specific Purposes around the world lead to the decision of analyzing a complex of factors that affect or hinder the effectiveness of the process of teaching and learning ESP courses at the University of Prishtina as well as at the private colleges in Kosovo. The research questions include: What are the problems faced by students learning ESP at the University of Prishtina and at the private colleges in Kosovo? What are the ways of solving these problems? etc. The data has been collected by conducting a survey in six academic units of the University of Prishtina including both teaching staff and student population. The selection of academic units is done on the bases of their specificity of the study field. That means the faculties that need a more specific vocabulary of English Language. There has also been conducted a survey in three private colleges considered as more successful colleges; “Dukagjini“ College, AAB College and the College “Biznesi”. Theoretical part is based on outstanding scholars and researchers of the English for Specific Purposes .Research findings have confirmed our research hypothesis displaying expected pattern of obstacles faced by the teaching staff and students in the process of teaching and learning ESP courses. Status of the course, large number of students in groups, lack of equipped laboratories and lack of qualified staff, present a hindrance in achieving the objectives of ESP courses at the University of Prishtina. While in private colleges it is students’ low knowledge of English language that prevents the teaching of English for Specific Purposes thus concentrating more on General English (GE).